Review of Cerliponase Alfa: Recombinant Human Enzyme Replacement Therapy for Late-Infantile Neuronal Ceroid Lipofuscinosis Type 2. (April 2020) - Lewis, Grace; Morrill, Amanda M.; Conway-Allen, Stephanie L.; Kim, Bernard
The objective of this review is to summarize the pharmacology, efficacy, and safety of cerliponase alfa for the treatment of late infantile neuronal ceroid lipofuscinosis type 2 (CLN2). Cerliponase alfa is recombinant human tripeptidyl peptidase 1 enzyme replacement therapy. A phase 1/2 trial established the efficacy and safety of cerliponase alfa for treatment of neuronal ceroid lipofuscinosis type 2. Treatment with intracerebroventricular cerliponase alfa resulted in slower decline of motor and language functions compared with natural history controls. Common adverse events include convulsions, electrocardiography abnormalities, pyrexia, vomiting, and upper respiratory tract infections. Intracerebroventricular device–related adverse events also occur. Cerliponase alfa is the first therapy for neuronal ceroid lipofuscinosis type 2 that targets the disease etiology. Cerliponase alfa is effective in delaying the progression of motor language decline for patients with neuronal ceroid lipofuscinosis type 2.